From TshwaneLex to TshwanePedia: Creating and Flexibly Maintaining Online Encyclopaedias - De Schryver, Gilles-Maurice; Joffe, David (Lexikos, 2005)
ABSTRACT: The addition of a restricted number of features to the dictionary (compilation) soft-ware TshwaneLex suffices to turn this application into a tool for the creation and maintenance of encyclopaedias. This article gives a brief overview of those extra features, using the online encyclo-paedia of the James Randi Educational Foundation (JREF) as case study.Keywords: LEXICOGRAPHY, DICTIONARY, ENCYCLOPAEDIA, SOFTWARE, ONLINE, TSHWANELEX, TSHWANEPEDIA, JAMES RANDI EDUCATIONAL FOUNDATION*****SAMEVATTING: Van TshwaneLex naar TshwanePedia: het samenstellen en flexibel herzien van on line encyclopedieën. De toevoeging van een beperkt aantal uitbreidingen aan de woordenboek(aanmaak)software TshwaneLex is voldoende om dit programma met succes voor de samenstelling en herziening van encyclopedieën in te zetten. Dit artikel geeft een kort overzicht van die extra uitbreidingen, en gebruikt de on line encyclopedie van de James Randi Educational Foundation (JREF) als illustratie.Sleutelwoorden: LEXICOGRAFIE, WOORDENBOEK, ENCYCLOPEDIE, SOFTWARE, ON LINE, TSHWANELEX, TSHWANEPEDIA, JAMES RANDI EDUCATIONAL FOUNDATION